Comparison of Website Maturity in e-Government Implementation at the City Level in Indonesia - Anggara, Reksi; Purnomo, Eko Priyo; Khairunnisa, Tiara (Journal of Government and Civil Society, 2024)
This study examines the e-government implementation in Indonesia, focusing on the comparative digital maturity of Bandung and Malang City. Employing a qualitative descriptive research methodology, this analysis primarily utilizes data from the official government websites, Bandung.go.id and Malangkota.go.id, both recognized for achieving high levels of digital maturity. The research aligns with the United Nations’ digital maturity evaluation criteria, scrutinizing key dimensions of e-government deployment. The findings reveal that both cities have established an integrated digital ecosystem that facilitates online services across various sectors. However, the arrangement of online services on the Malang City website lacks user intuitiveness, which may hinder public engagement. In terms of telecommunications infrastructure, Bandung City demonstrates superior performance, showcasing exceptional internet speeds, network coverage, and the availability of advanced technologies such as 4G+ and 5G. Both cities are committed to enhancing community internet access by providing free Wi-Fi initiatives. Furthermore, the study highlights substantial efforts by the local governments to improve human resource quality, evidenced by notable achievements in human resource management within their respective administrations. This research underscores the critical importance of digital maturity in enhancing public service delivery and promoting inclusive access to information technology in urban settings. Studi ini mengkaji implementasi e-government di Indonesia dengan fokus pada perbandingan kematangan digital Kota Bandung dan Malang. Menggunakan metodologi penelitian kualitatif deskriptif, analisis ini terutama memanfaatkan data dari situs web resmi pemerintah, Bandung.go.id dan Malangkota.go.id, yang keduanya diakui telah mencapai tingkat kematangan digital yang tinggi. Penelitian ini sejalan dengan kriteria evaluasi kematangan digital Perserikatan Bangsa-Bangsa, dengan memeriksa dimensi kunci dari penerapan e-government. Temuan menunjukkan bahwa kedua kota telah membangun ekosistem digital terintegrasi yang memfasilitasi layanan daring di berbagai sektor. Namun, pengaturan layanan daring di situs web Kota Malang kurang intuitif, yang dapat menghambat keterlibatan publik. Dalam hal infrastruktur telekomunikasi, Kota Bandung menunjukkan kinerja yang lebih baik, dengan kecepatan internet yang luar biasa, cakupan jaringan, dan ketersediaan teknologi canggih seperti 4G+ dan 5G. Kedua kota juga berkomitmen untuk meningkatkan akses internet masyarakat melalui inisiatif penyediaan Wi-Fi gratis. Selain itu, studi ini menyoroti upaya signifikan oleh pemerintah daerah untuk meningkatkan kualitas sumber daya manusia, yang dibuktikan dengan pencapaian penting dalam manajemen sumber daya manusia di masing-masing pemerintahan. Penelitian ini menekankan pentingnya kematangan digital dalam meningkatkan pelayanan publik dan mempromosikan akses informasi teknologi yang inklusif di lingkungan perkotaan